Implementasi Prinsip Hak Asasi Manusia dalam Proses Penyidikan di Indonesia - Afriani, Kinaria (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The enforcement of Human Rights in the investigation process in Indonesia is a crucial aspect in ensuring that the basic rights of individuals, especially suspects, remain protected during the criminal investigation stage. This article discusses the implementation of Human Rights principles reflected in the Indonesian legal framework, such as Law Number 8 of 1981 on the Criminal Procedure Code (KUHAP) and the Regulation of the Chief of the Indonesian National Police Number 8 of 2009. Although these regulations provide a foundation for the protection of Human Rights, the challenges of implementation on the ground remain significant. The obstacles faced by investigators in applying the principles of Human Rights include a lack of in-depth understanding among law enforcement officials, weak supervision, and limited facilities and infrastructure in various regions. The culture of violence, external pressure, and limited access to legal counsel also serve as hindrances. The importance of strengthening the capacity and awareness of law enforcement officers through training, enhanced supervision, and better coordination to ensure more effective protection of Human Rights in the investigation process.